Carbohydrate consumption among uncontrolled type 2 diabetes mellitus patients in Diabetic Clinic, Maharaj Nakorn Chiang Mai Hospital : การบริโภคคาร์โบไฮเดรตในผู้ป่วยเบาหวานชนิดที่ 2 ที่ควบคุมระดับน้ำตาลไม่ได้ - S, Kiewdee; B, Saengrut (Biomedical Sciences and Clinical Medicine, 2020)
Objectives To study carbohydrate intake in uncontrolled type 2 diabetes mellitus. This study is a descriptive cross-sectional study. Methods The samples were type 2 diabetic patients 150 people in Maharaj Nakorn Chiang Mai Hospital who were uncontrolled glucose levels with more than 7 percent hemoglobin A1 (HbA1c) from May to December 2019. The research instrument consisted of (1) The consumption interview form 24 hours dietary recalled record for three days, (2) Interview form for food consumption, which was developed by the Bureau of Nutrition, Department of Health. After collecting the data through the interview method, the researchers analyzed the nutritional data received using the NutriFacts program developed by the Nutrition Research Unit (NRU), Research Institute for Health Sciences, Chiang Mai University, Chiang Mai, Thailand. Data were presented by using descriptive statistics in a cross section (descriptive cross-sectional study). Results This study showed uncontrolled type 2 diabetes patients, consumed the average 3 - day carbohydrate equals to 252.02±52.58 grams, inclicating excessive carbohydrates intake when comparing to the recommended amount of carbohydrates that the patient should be received per days, and the amount of carbohydrates that should calculated from the total energy expenditure each day (TEE: total energy expenditure) in the proportion of food CHO : fat : protein = 50 : 30 : 20 when considering the frequency data of various daily consumption found. Daily consumption of carbohydrates, 64.4 percent eat white rice every day, 30.7 percent eat sticky rice every day. Snacks/sweets, found more than half of the samples did not consume at all, only 5.3 -6.7 percent consumed daily. For beverages, the sample group drank plain sweet coffee, iced tea, and little sweet coffee, iced tea every day 12.0, and 10.7% , respectively. For foods of dairy products, the sample group most consumed whole milk daily 24.7 percent. For foods that are sweet and citrus fruits found that daily consumption 10.0 and 5.3% respectively, most were consumed 2-4 times/week (67.3 and 48.0 percent respectively) as well as vegetables, sample group, eating fresh vegetables, and boiled vegetables every day, 18.7 and 19.3 percent respectively. Conclusion Patients with uncontrolled type 2 diabetes daily consumed excess carbohydrates. The results of the study can be used to plan nutritional education and consumption adjustment to improve the quality of care for diabetic patients in Maharaj Nakorn Chiang Mai Hospital.